Optimization of friction stir welding process to join dissimilar AA2014 and AA7075 aluminum alloys. (2022) - Haribalaji, V.; Boopathi, Sampath; Mohammed Asif, M.
Abstract: Friction stir welding (FSW) is an advanced welding process to join similar and dissimilar materials. The weld quality of FSW is mostly connected to input parameters and machine nature. In this research work, two dissimilar AA2014 and AA7075 aluminum alloys were welded in FSW using Taguchi design of experiments. The input parameters: tool rotation speed, welding speed, axial force, and tool tilt angle; Output parameters: Tensile Strength and Microhardness. The surface topography of tested specimens has been analyzed through Scanning Electron microscopic analysis (SEM). The analysis of variance (ANOVA) tests had been performed to find the significant factors to maximize the output responses. The maximum tensile 214 MPa was obtained from the best input parameters: 1000 rpm of rotating speed, 45 mm/min of weld speed, 6KN of axial force, and 2˚ of tool tilt angle. The optimum microhardness (132.5Hv) was predicted from 60 mm/min of weld speed.